2023
DOI: 10.1590/0001-3765202320220212
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of non-marine mollusks in the southernmost Paranaense forest of the world

Abstract: The Natural Reserve of Punta Lara (RNPL) is a protected natural area that includes Paranaense forest southernmost in the world. This area is surrounded by a densely populated and touristic sector. The objective of this work was to estimate the richness, diversity and equity of the RNPL mollusks (aquatic and terrestrial) and to establish the relationship of their species in aquatic environments. One sampling per year was carried out between 2013 and 2019. There were 32 species recorded (six are non-native speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…ituaRte (1981) suggested that both species of Corbicula were introduced between 1965 and 1975, while L. fortunei was detected in 1991, in each case following an increase in Argentinian imports from Hong Kong and Korea (daRRigRan & PastoRino 1995). Most likely they have been transported through interoceanic vessels in ballast tanks containing untreated freshwater, the most common cause of introduction of aquatic invaders worldwide (daRRigRan & PastoRino 2004, daRRigRan et al 2020, luCía et al 2023.…”
Section: Introductionmentioning
confidence: 99%
“…ituaRte (1981) suggested that both species of Corbicula were introduced between 1965 and 1975, while L. fortunei was detected in 1991, in each case following an increase in Argentinian imports from Hong Kong and Korea (daRRigRan & PastoRino 1995). Most likely they have been transported through interoceanic vessels in ballast tanks containing untreated freshwater, the most common cause of introduction of aquatic invaders worldwide (daRRigRan & PastoRino 2004, daRRigRan et al 2020, luCía et al 2023.…”
Section: Introductionmentioning
confidence: 99%